Centralizing the cult the holiness legislation in Leviticus 17-26 - Rhyder, Julia 1987- (Tübingen Mohr Siebeck, 2019)
Julia Rhyder untersucht in dieser Arbeit das Heiligkeitsgesetz (Lev 17–26) und die Frage nach der Kultzentralisation in der Perserzeit. Sie zeigt, dass Lev 17–26 die Vorstellung der Kultzentralisation nicht als etablierte Norm voraussetzt, sondern ein eigenständiges Verständnis von einem Zentralheiligtum, standardisierten Ritualen und einem hegemonialen Priestertum entwickelt.
In this work, Julia Rhyder provides new insights into the relationship between the Holiness legislation in Leviticus 17–26 and processes of cultic centralization in the Persian period. The author departs from the classical theory that Leviticus 17–26 merely presume, with minor modifications, a concept of centralization articulated in Deuteronomy. She shows how Leviticus 17–26 use ritual legislation to make a new, and distinctive case as to why the Israelites must defer to a central sanctuary, standardized ritual processes, and a hegemonic priesthood. This discourse of centralization reflects the historical challenges that faced priests in Jerusalem during the Persian era: in particular, the need to compensate for the loss of a royal sponsor, to pool communal resources in order to meet socio-economic pressures, and to find new means of negotiating with the sanctuary at Mount Gerizim and with a growing diaspora.
Überarbeitete Fassung der Dissertation
Literaturverzeichnis: Seite 409-450
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Ausbreitung des frühen Christentums; Forschungen zum Alten Testament; Sanctuary; Pentateuchal Theory; Priesthood; Priesthood; History of ancient Israel; Persian Period; Pentateuch; Centralization; Altes Testament; Antike; Array; Hochschulschrift